THE RIGHT TO JURIDICAL PERSONALITY OF ARBITRARILY DETAINED AND UNIDENTIFIED MIGRANTS AFTER THE CASE OF THE GUAYUBÍN MASSACRE - Campbell-Duruflé, Christopher (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2013)
In the Case of Nadege Dorzema et al v Dominican Republic, the Inter-American Court of Human Rights declined to make a finding of violation of Article 3 of the American Convention on Human Rights, the right to juridical personality. The author provides an analysis of this aspect of the judgment and argues that future cases of arbitrary detention of migrants, when these are not duly identified, provide strong bases for concluding in a violation of this right. The author shows that such circumstances correspond to the cases previously decided under article 3 of the American Convention, namely where the State puts individuals in a position where they are prevented from enjoying their civil rights, and were the State refuses to emit formal recognition of individuals or peoples. The author further shows how this conclusion is supported by the case law of the European Court of Human Rights regarding collective expulsions of migrants, because of this court’s special emphasis on their right to be duly identified and to an individualised evaluation of their case. The author concludes that finding a violation of Article 3 of the American Convention in future similar cases is necessary to give full meaning to this treaty and full effect to its regional specificity.